Antioxidant, Antiinflammation, and Antifibrotic Activity of Ciplukan (Physalis angulata L). Extract - Wiraswati HL; Ekawardhani S; Rohmawaty E; Laelalugina A; Zuhrotun A; Hendriani R; Wardhana YW; Bestari MB; Sahirdjan EH; Dewi S (Dove Medical Press, 2024)
Hesti Lina Wiraswati,1 Savira Ekawardhani,1 Enny Rohmawaty,1 Amila Laelalugina,2 Ade Zuhrotun,3 Rini Hendriani,4 Yoga Windhu Wardhana,5 Muhammad Begawan Bestari,6 Emmy Hermiyanti Sahirdjan,7 Sumartini Dewi7 1Department of Biomedical Sciences, Universitas Padjadjaran, Sumedang, West Java, Indonesia; 2Oncology and Stem Cell Working Group, Universitas Padjadjaran, Bandung, West Java, Indonesia; 3Department of Biological Pharmacy, Universitas Padjadjaran, Sumedang, West Java, Indonesia; 4Department of Pharmacology and Clinical Pharmacy, Universitas Padjadjaran, Sumedang, West Java, Indonesia; 5Study Center of Pharmaceutical Dosage Development, Department of Pharmaceutics and Pharmaceuticals Technology, Universitas Padjadjaran, Sumedang, West Java, Indonesia; 6Division Gastro Entero Hepatology, Department of Internal Medicine, Universitas Padjadjaran, Bandung, West Java, Indonesia; 7Department of Internal Medicine, Universitas Padjadjaran, Bandung, West Java, IndonesiaCorrespondence: Hesti Lina Wiraswati, Department of Biomedical Sciences, Faculty of Medicine, Universitas Padjadjaran, Sumedang, West Java, 45363, Indonesia, Tel +62-22-84288888, Fax +022-84288888, Email hesti.lina@unpad.ac.idPurpose: Physalis angulata Linn. (Ciplukan) is a plant widely used in traditional medicine in subtropical and tropical regions. Most studies focus on its antioxidant and anti-inflammatory activity. Many studies also reported its therapeutic potential for treating cancer, malaria, hepatitis, rheumatism, liver problems, and tumors, but few studies have reported its anti-fibrosis activity. Here, we aimed to investigate the potential of P. angulata as an antioxidant and anti-inflammatory that may be correlated with its anti-fibrosis action.Methods: In our study, we treated 3T3-L1 and TGF-β-induced 3T3-L1 cells with an ethanol extract of P. angulata. We then monitored the cell's response, evaluated the antioxidant activity using an MTT assay, and observed the cells' migration using the cell scratch assay. We used RT-PCR to determine the expression of HIF-1α and IL-6 on TGF-β-induced 3T3-L1 cells.Results: The ethanol extract of P. angulata showed antioxidant activity and promoted cell proliferation on 3T3-L1 cells. Interestingly, the extract inhibited the migration of TGF-β-induced 3T3-L1 cells. Further analysis revealed that the extract could inhibit HIF-1α expression and suppress IL-6 expression on TGF-β-induced 3T3-L1 cells.Conclusion: The ethanol extract of P. angulata showed antioxidant and anti-inflammation activities in 3T3-L1 cells. Both activities are associated with the antifibrotic activity of P. angulata's ethanol extract.Keywords: TGF-β, ethanol extract, wound healing, fibroblast cell line